The Role of Imagery and Experiences in the Construction of a Tourism Destination Image - Matos, Nelson; Mendes, Júlio; Pinto, Patrícia (Journal of Tourism, Sustainability and Well-being, 2015)
This paper addresses the role of imagery and tourism experiences (TEs) in the construction of tourism destination image (TDI). It highlights the importance of the construct imagery at all stages of consumption, because of the intangibility that characterizes tourism and services in general. This aspect gains importance since it is impossible for tourists to experience the desired holidays prior to visitation, leading the way for imagery to become an essential element to inspire and to influence them during the decision-making process, and consumption before, during and after the experience. A conceptual model resulting from the literature review and the potential theoretical contribution of the model are discussed.